A National Study on Employee Motivation In Cross-Cultural Companies: - (Journal of Advances and Scholarly Researches in Allied Education, 2014)
With the fast growing economic and globalization, there is a growth inthe multinational companies and cross-cultural business communication isgetting increasingly significant. Nowadays, it is quite common to see employeesfrom different cultures or different countries working in the same company,even in the same office. Cross-cultural corporations are compelled to work hardin order to improve their core competence as well as develop their competitiveadvantages due to severe global competition. As a matter of fact, in a crosscultural organization, there could be so many problems, such as culturecollision, communication disorder etc., which might make big troubles for thehuman resource department, and even worse affect the working efficiency of acompany in the long run. Hence, for the human resource management department, amotivated working group is urgently required. Keywords: Motivational Factors,Dimension of Culture, Coping strategy.